ANALISIS STRATEGI PENGEMBANGAN AGRIBISNIS KARET RAKYAT DI KABUPATEN KUANTAN SINGINGI, PROVINSI RIAU - Hajry Arief Wahyudy; Azharuddin Azharuddin; Asrol Asrol (UIR Press, 2015)
Rubber plantation in Kuantan Singingi Regency needs to pay attention in order to give so a great impact for farmers’ welfare. Therefore, the strategy of rubber development by agribusiness-oriented become increasingly important. The purpose of this study was to analyze characteristics of the farmer, to highlight agribusiness system, and to make a strategic development of smallholder rubber agribusiness. The method used in this study was survey. The data used were primary and secondary data and then were adjusted to the needs of research v. Data were analyzed by descriptive quantitative and used SWOT Analysis. The results showed that the ability of farmers in rubber farming was dominated by productive age ranges with the education level of elementary school. This will be impacted on mindset primarily in making farm management decision. Management of smallholder rubber agribusiness system is not currently well integrated, each subsystem needs to get a referral to a policy binding so that the performance of each subsystem can be optimized. SWOT analysis directs agribusiness development strategy of smallholder rubber in Kuantan Singingi growth strategies, ie the quadrant WO (Weakness-Opportunity), so that the internal weakness of agribusiness system must be completed to take advantage of greater opportunities in the future.